1971
DOI: 10.1002/jsfa.2740220510
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of three albumins from Triticum aestivum seeds

Abstract: Three albumins were isolated from bread wheat seeds by gelfiltration on Sephadex G-100 and differential preparative disc-electrophoresis on polyacrylamide gel. The proteins were obtained in suficient yield and purity to carry out characterisation studies. The electrophoretic mobilities of the three albumins in polyacrylamide discs in glycine- Tris medium, p H 9.5, were 0.28, 0.34 and 0.39 (referred to that of bromophenol blue taken as I ) . The isoelectric points were 6'40, 6.40 and 5.35 and the molecular we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Since then several workers have studied the a-amylase inhibitors in wheat (Shainkin and Birk 1970;Silano et al 1973; Saunders and Lang 1973;Petrucci et al 1974Petrucci et al ,1975Buonocore et al 1976;De Ponte et al 1976). Earlier, others had worked on the same wheat albumins without knowing that they had the ability t o inhibit a-amylase (Nimmo et al 1963; Fish and Abbott 1969;Ewert 1969; Feillet and Nimmo 1970;Sodini et al 1970; Cantagalli et al 1971). Shainkin and Birk (1970) purified and characterized two different a-amylase inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Since then several workers have studied the a-amylase inhibitors in wheat (Shainkin and Birk 1970;Silano et al 1973; Saunders and Lang 1973;Petrucci et al 1974Petrucci et al ,1975Buonocore et al 1976;De Ponte et al 1976). Earlier, others had worked on the same wheat albumins without knowing that they had the ability t o inhibit a-amylase (Nimmo et al 1963; Fish and Abbott 1969;Ewert 1969; Feillet and Nimmo 1970;Sodini et al 1970; Cantagalli et al 1971). Shainkin and Birk (1970) purified and characterized two different a-amylase inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Gel electrophoresis has been used extensively to characterize and identify proteins and enzymes in biological systems (Cantagalli et al, 1971;Cherry et al, 1970Cherry et al, , 1971aCherry et al, ,b, 1972Dawson, 1971 Tombs, 1963) and to detect experimentally induced modifications in these molecules (Jensen, 1959;Neucere, 1972;Neucere et al, 1972). Cherry et al (1971b) and Cherry and Ory (1973a,b,c) have shown that the electrophoretic protein and enzyme profiles of individual peanuts are very complex, with much variation within the cultivars examined.…”
mentioning
confidence: 99%
“…No. P01083), also known as inhibitor 0.28 based on its electrophoretic mobility on native PAGE (7.5% acrylamide disc electrophoresis; Cantagalli et al 1971). De novo sequencing of the fraction 3 main component allowed to determine the sequence reported in Fig.…”
Section: Inhibitor(s) Sequencing and Identificationmentioning
confidence: 99%